The Mental State of Parents in Diseases of Young Children - Solondaev, V.K.; Pisareva, M.V. (Autizm i narušenie razvitiâ, 2024)
Objectives. Children's illnesses negatively affect their mental and physical development, causing anxiety and psychological discomfort to parents, since increased demands are placed on parental care. In turn, the discomfort of the parents increases the risk for the normal development of the child. In the Yaroslavl region, about 7% of all younger aged children are hospitalized annually. Of these, 97% are initial, 8% are in serious condition. Researchers describe relatively stable psychological characteristics of parents of sick children. In order to psychologically optimize the treatment process, the previously undescribed psychological state of mothers of infants hospitalized with their children in the Yaroslavl Oblast Children's Clinical Hospital health care institution was investigated. Methods. The sample consisted of 34 women hospitalized with their children under 3 years of age. Using the "Layout of the mental state" method by A.O. Prokhorov, three mental states were assessed: the actual state at the time of the research, the habitual state and the state at the onset of the child's disease. The state of health of the child was also assessed by the respondents on a scale from 0 to 10. The data covering the period of 2019-2023 hospitalizations of the children of early age were used. Results. The actual mental states reported by respondents were significantly worse than their habitual ones, according to descriptor groups Psychic Processes and Feeling. The actual mental states were better than the ones at the onset of disease, according to descriptor groups Psychic Processes, Physiological Reactions, Feeling and Behavior. The evaluation of a child's health is associated only with a change in the state of the group of Mental processes descriptors (Kendall's Tau 0.30; z = 2.4; p-value = 0.02). Conclusions. Two opposite changes in the mental state of mothers during hospitalization of children were revealed: the worsening compared with the usual state, improvement in the mental state compared to the onset of the child's disease. Changes in mental state in seven of the eight groups of descriptors are independent of the parents' assessment of the child's health at the time of the examination. A small sample implies a special assessment of the sustainability of the results. Актуальность и цель. Болезни детей негативно влияют на их психическое и физическое развитие, вызывая тревогу и психологический дискомфорт родителей, поскольку к родительской заботе предъявляются повышенные требования. В свою очередь, дискомфорт родителей усиливает риск для нормального развития ребенка. В Ярославском регионе ежегодно госпитализируется около 7% всех детей раннего возраста. Из них 97% первично, 8% в тяжелом состоянии. Исследователи описывают относительно устойчивые психологические характеристики родителей болеющих детей. С целью психологической оптимизации лечебного процесса исследовалось не описанное ранее психическое состояние матерей детей раннего возраста, госпитализированных с детьми в учреждение здравоохранения Ярославской области «Областная детская клиническая больница». Методы и методики. В исследовании участвовали 34 женщины, госпитализированные с детьми в возрасте до 3-х лет. По методике «Рельеф психического состояния» А.О. Прохорова оценивались три состояния: актуальное на момент исследования, обычное и состояние на момент начала болезни ребенка. Кроме своего психического состояния, испытуемые оценивали состояние здоровья ребенка на момент исследования по шкале от 0 до 10. Также обрабатывались документальные данные о госпитализации детей раннего возраста за 2019-2023 годы. Результаты. Актуальное на момент госпитализации ребенка состояние переживается матерями как статистически значимо худшее, чем обычное, - по группам дескрипторов Психические процессы и Переживание. Актуальное состояние оценивается как лучшее, чем состояние на момент начала заболевания, - по группам дескрипторов Психические процессы, Физиологические реакции, Переживание, Поведение. С оценкой здоровья ребенка связано только изменение состояния матерей по группе дескрипторов Психические процессы (Тау Кендалла 0,30; z = 2,4; p-value = 0,02). Выводы. Выявлены два противоположные изменения психического состояния матерей при госпитализации детей: ухудшение по сравнению с обычным состоянием и улучшение состояния по сравнению с началом заболевания ребенка. Изменения психического состояния по семи из восьми групп дескрипторов не зависят от оценки родителями здоровья ребенка на момент обследования. Малая выборка предполагает в дальнейшем работу по специальной оценке устойчивости результатов.